Proposed new interior design for Lotus Racing Cafe at K-09-12, No 1, Jalan Solaris, Solaris Mont Kiara, 50480, Kuala Lumpur / Mohd Hasrul Mohd Mubarak - Mohd Mubarak, Mohd Hasrul (Faculty of Architecture, Planning and Surveying, 2011)
The project title for my final project is Proposed New Design For Lotus Racing Cafe at K-09-12, No.1, Jalan Solaris, Solaris Mon’t Kiara, 50480, Kuala Lumpur. Last year, in 2010,It is the year that Lotus Racing had rejoin the F1 race with new machine and racers. As we known the founder of the team was Dato’ Fernandez, Proton Malaysia and 1 Malaysia F1 Team Sdn. Bhd and by using ‘Lotus Racing’ as their F1 team is the client of this project and it is my obligation to solve their problem, which is creating new look or image for their cafe that focusing on race, entertainment, interactive and full of enjoyment. Solaris Mon’t Kiara or SohoKL has been chosen as the site for project because the site is situated in the most strategic area. It have a lot of beautiful surrounding and facilities. It would not be a problem to setup a new place such as a Cafe. As we known, cafe is an informal restaurant which is offering a range of hot meals and made-to-order like sandwiches. A cafe should be a nice place to will give pleasure and excitement to their fans. Which was also the main reason why the project being proposed. So, the cafe must be design according to a concept and images that related to my client. A few methods had being use in order for the project to be success such as research, interview, site visiting and a lot more in order to finish the design process.